Behind closed doors : sex education transformed - Fiennes, Natalie (London : Pluto Press, 2019)
One thing we know for certain is that sex is personal: perhaps the most intimate thing of all. But sex is also shaped by a complicated web of cultural, social and political forces outside of ourselves.0Fear-mongering, moral panic and outdated attitudes prevail, but if #MeToo has taught us anything, it's how dangerous it is to keep conversations about sex hidden from view. Behind Closed Doors invests in a radical, inclusive and honest sex education, taking us beyond learning about the 'birds and the bees', to identifying inequality that stands in the way of sexual freedom.0From contraceptives to virginity, consent to pornography, transphobia to sexual abuse, the book shows how our desires are influenced by powerful political processes that can be transformed.
Includes bibliographical references.
Keywords: Sex instruction -- Political aspects; Sex instruction -- Social aspects; Sexual freedom; Intimacy (Psychology); Intimacy (Psychology); Sexual freedom